Objective‐driven process appraisals: an educational experiment. Issue 11 (17th October 2016) - De Man, Jozef
Abstract: Software improvement frameworks are often perceived to be expensive and oriented toward larger companies. It is also difficult to teach these frameworks to students who lack any experience with software development in a commercial setting. In this paper, we report experience with teaching software process improvement by using a series of small exercises that together establish a quick objective‐driven appraisal of a software organization. We show how the focus on practical results reinforces the educational value of the exercise by making it more engaging for students.